A new species of Gymnophthalmus (Squamata: Gymnophthalmidae) from sand dunes of the Llanos of Apure, Venezuela - García-Pérez, Juan E.; Schargel, Walter E. (Zootaxa, 2017)
A new species of Gymnophthalmus is described from the Llanos of Venezuela in Apure State. Gymnophthalmus marconaterai sp. nov. is found mostly on sand dunes and is seemingly endemic to the eolic plains of Apure State. The new species differs from all other species of Gymnophthalmus with 13 scales around the midbody, by having distinctive coloration that includes complete and well-defined lateral and dorsolateral white stripes, a white ventral coloration in preservative (creamish white or yellow in life) devoid of dark markings, and salmon pink tail in life.